2020
DOI: 10.1186/s12911-020-01347-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active occupational stress management on psychosocial and physiological wellbeing: a pilot study

Abstract: Background The aim of the study was to address the working population with an occupational stress prevention program using mHealth solution and encourage them for healthy lifestyle choices. Methods Seventeen participants were randomized from the corporate setting. A 24alife app with a good compliance program was selected. Test battery has been designed to test the physical readiness, psychological evaluation and biological blood markers for stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The impact of digitalization can affect cognitive processes which are considered as psychological responses to prolonged stress and are usually expressed by negative emotions such as anxiety, depression, and anger. (Jukic et. al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of digitalization can affect cognitive processes which are considered as psychological responses to prolonged stress and are usually expressed by negative emotions such as anxiety, depression, and anger. (Jukic et. al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a recent study found that more than half of the US workforce felt burned out and 40% were considering changing jobs to resolve stress ( Talkspace, 2021 ). While the influence of occupational-related stress on the health of workers is increasingly being recognized ( Kinnunen-Amoroso and Liira, 2014 ; Bruschini et al , 2018 ; Jukic et al , 2020 ; Doyle et al , 2021 ), relatively little research has been conducted with a focus on how the ongoing pandemic has exacerbated these occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…While the influence of occupational-related stress on the health of workers is increasingly being recognized [37][38][39][40][41][42], to date, relatively little research has been conducted with a focus on longitudinal salivary cortisol collection in conjunction with the documentation of daily stressor events. One study, by Eller et al (2006), used survey response answers to describe participants, i.e., age, smoking status, children, and work-related questions, to name a few, but the lack of a diary limited the ability to truly connect cortisol fluctuations with what the participant was exposed to at a given time, on a given day [43].…”
Section: Introductionmentioning
confidence: 99%